Development of the top level of the automated SCADA system of feeding moisture in the soil-vegetative cover - Belei, Oksana; Zamikhovska, Olena; Stasyuk Rоman (Technology audit and production reserves, 2017)
The developed automated SCADA system of water supply to the soil and vegetation cover will allow to control and select the optimal mode of water supply in order to improve the yield and provide plants with water. The water supply system has a number of advantages: – system availability; – support for various industrial communication interfaces; – convenience in use; – universality; – possibility of developing graphic models . Currently, additional functions (tags) are connected in the system, which are responsible for collecting current information about the operation of the equipment with the darling alarms, the primary transformation of the collected information; presentation of current information in the form of histograms, tables, graphs; printing of reports and protocols on the operation of equipment units and organization of communication with devices connected to the information display of data archiving and possible revision on-line.